Coconut Water as Organic Inhibitor on Corrosion of Low Carbon Steel in 3.5% NaCl Solution - Magga, Ramang; Zuchry, Muhammad; arifin, Yusnaini (Politeknik Negeri Ujung Pandang, 2020)
Investigating coconut water as inhibitors to protect low-carbon steel from corrosion in 3.5% NaCl has been studied by weight loss method. The weight loss of steel was identified by immersion test. The coconut water used was young and old coconut water. The concentration of coconut water, whether young and old, in 3.5% NaCl was varied. The results showed that the corrosion rate of steel decreased with increasing coconut water concentration. Furthermore, old coconut water can further reduce the rate of corrosion in mild steel comparing young coconut water.